A time series analysis of mineral revenue and economic growth in Ghana - Frank Boateng; Gomashie Edem Wisdom; Sulaiman Olusegun Atiku (Cogent Economics & Finance)
Mineral revenue is a vital source of revenue for the Government of Ghana, making it essential to assess its impact on economic growth. This study examines the long-term relationship between mineral revenue, government expenditure (GE), foreign direct investment (FDI), and economic growth in Ghana from 1990 to 2019. Utilising a quantitative approach, data was sourced from the Minerals Commission, the Bank of Ghana, the Ghana Chamber of Mines, and World Development Indicators. The study employed techniques such as the Vector Error Correction Model, Granger Causality, variance decomposition, and VAR for time series data analysis. Cointegration results indicated at least one cointegrating equation, revealing a long-term economic relationship among the variables. The findings suggest that mineral revenue positively correlates with economic growth (measured as real GDP), while FDI and GE exhibit negative relationships with real GDP. Notably, the inverse correlation between GE and real GDP implies that public spending may not be effectively directed toward sectors that significantly enhance economic growth. Overall, the study confirms that mineral revenue is a key contributor to Ghana's GDP and highlights that shocks to the mining industry could have substantial repercussions for the economy.